MANTLE CELL LYMPHOMA PATIENT WITH SKIN GVHD AFTER AUOTOLOGOUS STEM CELL TRANSPLANT - Mehmet Sezgin Pepeler; Merve Pamukçuoğlu; Gulsum Özet; Simten Dağdaş; Funda Ceran; Beytullah Altınkaynak (Hematology, Transfusion and Cell Therapy)
Objective: Graft-versus-host disease (GVHD) after ASCT is an immunologically developing process. T cells and inflammatory cytokines formed against the recipient'ss alloantigens are responsible for this. It is less common in autologous SCT than in allogeneic SCT. It has been reported in the literature that there are MM patients who developed autologous GVHD after Auotologous SCT. Case report: Here, we present a case of mantle cell lymphoma who developed autologous GVHD after ASCT, not previously reported. Fifty-four-year-old male patient was diagnosed with Stage 4A Mantle cell lymphoma according to the Ann Arbor staging system based on the result of inguinallymph node excisional biopsy performed in July 2021. Three courses of R-CHOP,DHAP treatment was started for the patient who did not respond after R-CHOP treatment. Complete response was achieved after three cycles of R-DHAP therapy,and mobilization was performed with filgrastim and plerixafor protocol. Then, autologous SCT was performed with the BEAM protocol(Karmustine 300mg/m2, Etoposide 200mg/m2, Cytosine Arabinoside 2 × 100mg/m2, Melphalan 140mg/m2). Post-transplant neutrophil engraftment occurredon the+14th day and platelet engraftment on the +32nd day. Piperacillin Tazobactam was started due to fever and sore throat on the 3rd day of ASCT. Teicoplanin was added to the treatment after the fever persisted on the 5th day of ASCT. Piperacillin Tazobactam treatment was discontinued due to acute phase reactant increaseand fever on ASCT +7th day and Meropenem was started. Teicoplanin treatment was stopped on the +16th day after transplantation, and Meropenem was stopped on the +17th day. On the +14th day of autologous SCT, complaints of itching and rash started on the patient's body The biopsy result of the patient who underwent skin biopsy was compatible with grade 1-2 GVHD The patient was started on high-dose corticosteroid therapy. On the+21st day, the complaint of itching and on the +28th day, the skin findings disappeared. On the +28th day of ASCT, corticosteroid therapy was tapered and discontinued. The patient is still being followed without disease. Conclusion: Autologous GVHD is an autoimmune syndrome initiated by autoreactive T cells that recognize major histocompatibility complex (MHC) class II antigens.CD8+ T cells recognize MHC class II determinants .There are three types of autologous GVHD: 1. spontaneous autologous GVHD 2.induced autologous GVHD; using cyclosporine, tacrolimus, interferon-α, interferon-y and alemtuzumab to induce the effect of GVT; GVHD induced by transfusion of non-irradiated blood products in patients with Hodgkin lymphoma, Non-Hodgkin Lymphoma (NHL), chronic lymphocytic leukemia, and acute myeloid leukemia 3. induced by transfusion of non-irradiated blood products.In the study of Drobyski et al. in 2008, it was reported that autologous GVHD developed in 5 of 386 patients who underwent autologous SCT. Response to steroids was not good. It was the first transplant of 223muliple myeloma patients. Only 2 patients developed autologous GVHD. Autologous GVHD developed in 3 of 27 patients with a second transplant.Autologous GVHD did not develop in Hodgkin lymphoma, non-Hodgkin lymphoma and AML patients. Therefore, it will be important to consider this complication while planning the second autologous stem cell transplant in these patients .Our case presents skin GVHD developing after autologous SCT. However, since our patient has lymphoma and/or did not take a proteasome inhibitor before, it is important by distinguishing it from other cases.When the literature is examined, it is thought that the preparation regimens and post-transplant CsA application prepare the ground for autologous GVHD In addition, it is known that patients with hematological malignancies who are female, given high-dose CD34+ stem cells,bortezomib, lenalidomide, pomalidomide and alemtuzumab used in their pre-transplant treatments are at risk for autologous GVHD.